Bakhtin Attends the Theater: Kama Ginkas's Chekhov Trilogy. Issue 2 (April 2016) - BISHOP, SARAH CLOVIS
Abstract : In the late nineties and early 2000s, Kama Ginkas, one of the most celebrated theater directors working in Russia today, staged three Chekhov stories: "Lady with the Lapdog, " "The Black Monk, " and "Rothschild's Fiddle. The actors give voice to virtually every word of the literary texts, even in the form of spoken stage remarks such as "he said" and "she said." While the shows are performed independently, Ginkas views them as a trilogy which he has titled Life is Beautiful . According to Ginkas, the central narrative thrust of all three shows, and of Chekhov's work in general, is man's desire and failure to live life fully. He highlights the Chekhovian tension between the beauty of life and the tragedy of how it is lived. Drawing on Bakhtinian concepts, this article examines how Ginkas's trilogy reveals but does not resolve this terribly beautiful nature of life. By placing Chekhov's narration into the mouths of his actors, Ginkas actualizes the character zones found in Chekhov's authorial prose. This does not result in a flattening of the voices, as Bakhtin had feared; instead, Ginkas actively dialogizes the voices through the use of interruptions, repetitions and incongruities between word and action. Ginkas further activates Chekhov's language by inserting excerpts from an early Chekhov feuilleton, folk songs, and opera into the performances. Through this reaccentuation of the prosaic text and the heteroglossic interpolation of additional texts, Ginkas repeatedly and unexpectedly shifts between the tragic and the comic, the terrible and the beautiful, highlighting the unfinalizability of his performed prose.